"Against the tidal forces of the day": idiorrhythmy, syncopated subjects and the non-assimilative community in the work of Erika Vogt and Jérôme Bel. Issue 1 (3rd April 2018) - Willis, Emma
ABSTRACT: In How to Live Together, Roland Barthes evokes a utopian form of cohabitation "where each subject lives according to his own rhythm […] idiorrhythmy." This essay considers how Jerome Bel's Ballet and Erica Vogt's Lava plus Knives may be read as idiorrhythmic clusters that resist the unified rhythm of consensus, and in so doing enact non-assimilative communities of aesthetic practice. With reference to Roberto Esposito's definition of communitas as, "a dizziness, a syncope, a spasm in the continuity of the subject, " these communities are characterized as conceptually noisy and politically disruptive in their embrace of simultaneous differential rhythms.